SIMPLIFYING SHIP STRUCTURAL OPTIMIZATION THROUGH STRESS-BASED MATERIAL SELECTION - Putra, Gerry Liston; Fahryansyah, Muhammad Rakan; Riadi, Achmad; Budiyanto, Muhammad Arif; Nugroho, Firman Ady (Journal of Applied Engineering Science, 2025)
The structural integrity of a ship emerges as a crucial factor that significantly impacts the overall weight of the ship's construction. When evaluating ships with identical shapes, a strategically refined structural design can greatly amplify the ship's load-bearing capacity. This optimization, in turn, wields a profound influence over the ship's operational efficiency and its broader environmental impact. A highly successful strategy for achieving structural optimization revolves around the meticulous selection of materials that align with permissible stress thresholds mandated by regulations. This selection process is guided by thorough finite element analysis. Within this study, the pursuit of optimization unfolded through an examination of material variations. The initial phase involves the application of diverse material options for each design iteration while adhering to the minimum thickness stipulated by the classification society's regulations. This iterative process persists until the thickness aligns with the structural requirements necessary to uphold load-bearing resilience. The outcomes of this initial step subsequently provide insights into the possibility of substituting materials with higher-ranked alternatives. The material ranking is established by comparing their yield strengths. The materials investigated in this research encompass Mild Steel, AH32, and AH36. The findings of this study underscore the capacity of thickness optimization to significantly reduce the weight of a ship's construction.
Keywords: optimization, material selection, thickness, weight, stress